Association between hypomineralization of deciduous and molar incisor hypomineralization and dental caries - Quintero, Yasmy [UNESP]; Restrepo, Manuel; Rojas-Gualdrón, Diego Fernando; de Farias, Aline Leite [UNESP]; Santos-Pinto, Lourdes [UNESP] (FapUNIFESP (SciELO), 2022)
This study aimed to evaluate the association between the severity of hypomineralized second primary molars (HSPM), molar-incisor hypomineralization (MIH) and dental caries in children. 450 children between the ages of 6 and 7 years were included in this cross-sectional study. A calibrated examiner classified the enamel hypomineralizations and dental caries lesions using the MIH and HSPM and the Nyvad criteria, respectively. The primary outcome was the severity of MIH according to the severity of HSPM. Statistical analysis was performed using the generalized linear model and ordinal logistic regression. The prevalence of concomitant MIH and HSPM was 26% sex and age adjusted. Mild enamel defects were more frequent than severe enamel defects. An association was found between the severity of MIH and HSPM, both for mild defects (OR=87.54; 95%CI: 55.87, 137.17) and severe defects (OR=82.15; 95%CI: 45.72, 147.61). The severity of hypomineralization in permanent molars was associated with the activity of dental caries lesions (OR=29.85; 95%CI: 12.95, 68.83). To conclude, there is a strong association between the severity of HSPM and MIH, which is more significant in the presence of active dental caries lesions.
Keywords: Dental care; dental caries; dental enamel; molar incisor hypomineralization; primary teeth